PENGARUH E-SERVICE QUALITY, FOOD QUALITY, DAN CUSTOMER SATISFACTION MELALUI PERCEIVED VALUE TERHADAP BEHAVIORAL INTENTION PADA PELANGGAN GOFOOD DI WILAYAH DKI JAKARTA - Yulianti, Bunga Asri; Satya, Irma (Solusi, 2021)
The purpose of this study is to know the influence effect of E-Service Quality, Food Quality, and Customer Satisfaction through Value on Behavioral Intention to Gofood customers in DKI Jakarta area.The design in this study used descriptive research and causality research, each variable in this study was measured using a 5-point likert scale. This study used primary data collected by using a questionnaire. The sample in this study was obtained through purposive sampling method and obtained as many as 216 respondents. The statistical method used in this study is SmartPLS 3.2.9 as a test tool.The results of this study indicate that E-Service Quality, Food Quality, Customer Satisfaction, and Value have an influence on the Behavioral Intention of Gofood customers in the DKI Jakarta area. Meanwhile, Food Quality has no effect on the Customer Satisfaction of Gofood customers in the DKI Jakarta area.Keywords: E-Service Quality, Food Quality, Customer Satisfaction, Value, Behavioral Intention.